LAPORAN KASUS LOW BACK PAIN PADA OPERATOR BULLDOZER - Febrina Emanuela; Chikita Nur Mustika Rahmaditya; Alvin Mohammad Ridwan (Fakultas Kedokteran Universitas Trisakti, 2025)
Low back pain (LBP) is a common health problem in the workplace and most workers are expected to experience symptoms of low back pain during their working lives. Statistics in the United States show an incidence of 15%-20% per year. Some jobs that have high exposure to vibration such as heavy equipment operators, machinists, and truck drivers can also increase the likelihood of LBP. This paper reviews LBP in operators. Bulldozer with a focus on occupational medicine-based approaches in prevention and treatment. A 45-year-old man who works as an operator Bulldozer reported experiencing pain in the lower right back since one month ago which worsened in two weeks. Physical examination confirmed the diagnosis of LBP. Complaints are felt more severely when the patient sits for a long time and when the patient is bending his back. The patient has worked as a Bulldozer operator for the past 4 years and complaints are aggravated when the patient performs duties as an operator bulldozer while sitting upright for 9 hours per day. LBP risk management includes Technical Controls and Administrative Controls. Length of work > 4 years as an operator Bulldozer supports the event Low back pain (LBP). Sitting for > 4 hours also carries the risk of causing lower back pain. It can be concluded that the diagnosis of LBP in this case can be closely related to work as an operator bulldozer. The combination of non-ergonomic working positions, long working hours and vibrations leads to the diagnosis in this patient of acute low back pain